2016
DOI: 10.1371/journal.pone.0163288
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of mTORC1 Activity in CD4+ T Cells Is Associated with Lung Fibrosis and Increased γδ T Cells

Abstract: Pulmonary fibrosis is a devastating, incurable disease in which chronic inflammation and dysregulated, excessive wound healing lead to progressive fibrosis, lung dysfunction, and ultimately death. Prior studies have implicated the cytokine IL-17A and Th17 cells in promoting the development of fibrosis. We hypothesized that loss of Th17 cells via CD4-specific deletion of mTORC1 activity would abrogate the development of bleomycin-induced pulmonary fibrosis. However, in actuality loss of Th17 cells led to increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 29 publications
(47 reference statements)
0
7
0
Order By: Relevance
“…The protective roles of Tregs were regulated by mTOR in the repair of acute kidney injury [ 104 ]. Moreover, deletion of mTORC1 activity in CD4 + T cells resulted in increased inflammation, accelerated fibrosis development and increased mortality, which was associated with IL-17 production derived from γδT cells [ 136 ].…”
Section: The Molecular Mechanisms Of Immune-mediated Signaling Patmentioning
confidence: 99%
“…The protective roles of Tregs were regulated by mTOR in the repair of acute kidney injury [ 104 ]. Moreover, deletion of mTORC1 activity in CD4 + T cells resulted in increased inflammation, accelerated fibrosis development and increased mortality, which was associated with IL-17 production derived from γδT cells [ 136 ].…”
Section: The Molecular Mechanisms Of Immune-mediated Signaling Patmentioning
confidence: 99%
“…Jin et al ( 29 ) implicated that commensal-bacteria activated γδ T cells in lung tissue and promoted lung adenocarcinoma through IL 17 production. Data in Vigeland’s study elucidate the critical role of IL 17A + γδ T cells in promoting chronic inflammation and fibrosis of the lung tissue ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Generally, IL 4, IL10, and IL 13 are considered the more common markers for inducing M2 polarization; however, existing studies have shown that in the lung tissue, γδ T cells could regulate M2 polarization of macrophages by producing IL17 and that M2 polarization could be significantly inhibited if γδ T cells was deficient or IL17 was blocked. In lung tissue, IL 17 expressed by activated γδ T cells could induce macrophage proliferation and M2 polarization, thus further affect disease progression ( 30 , 38 , 39 ). This procedure had been demonstrated in both pulmonary inflammation and lung fibrosis ( 38 , 39 ) as well as in OSCC with periodontitis models ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations